Evaluasi Beberapa Nomor Aksesi Kentang (Solanum tuberosum L.) Terhadap Ketahanan Penyakit Hawar Daun (Phytopthora infestans (Mont.) de Bery) - Muhamad Yusuf (Agrium, 2018)
The purpose of this study is to evaluate 27 potato accession numbers from crosses that have disease resistance of  P. infestans ( late blight ), knowing the potential production of 27 clones of potato accession numbers from crosses. Results showed the intensity of the disease are observed including six resistant clones 22.22% (PT4, AP3, PT3, AP4, AP7, and PT2) with the intensity of attacks between 9.70-18.33%, 14.81% four moderately resistant clone (PT1, PT5, AP8 and AP2) with the intensity of 20.48-37.50%, 12%  moderately susceptible clones 44.44 (RP5, RP18, RP7, RP16, RP 6, RP 8, RP3, RP2, RP14, RP17, Rp13, and RP10) with the intensity of attacks 45.00-59, 12%, and 18-52% five clones were classified as susceptible (RP4, RP15, RP 9, AP1 and AP6) with the intensity of attacks between 68.18-100%. Intensity of the relationship is linear with the number of bulbs, with the model equation Y = 17 594 - 0.174x. (R2 = 0.264), the intensity of the relationship with tuber weight is linear, with the model equation Y = 404 817-4.606x. (R2 = 0.297) and the intensity of the bulb volume is linear, with a regression model Y = 346 010- 4.081x. (R2 = 0.292).